Porous polydimethylsiloxane composite filled with graphene oxide and gold nanoparticles produced by laser ablation in liquids. (May 2022) - Cutroneo, M.; Havranek, V.; Torrisi, L.; Silipigni, L.; Kovacik, L.; Malinsky, P.; Slepicka, P.; Fajstavr, D.; Janoušková, O.; Zbořilová, D.; Mackova, A.
Abstract: The design of new materials with improved mechanical and biological properties is a major interest in biomedical applications. This paper presents the synthesis of macro-porous polydimethylsiloxane (PDMS) sponge composites as potential materials for tissue engineering. PDMS sponge with pores size ranging between 50 and 900 μm was produced using the sugar templating process. The sponges were decorated with graphene oxide and gold nanoparticles created by the laser ablation in liquid and then they were morphologically, mechanically and biologically characterized. The optical properties of all the solutions containing nanoparticles were studied with the UV-ViS spectroscopy. The biological behaviour and performance of native PDMS, PDMS decorated with graphene oxide, and with graphene oxide and gold nanoparticles were compared. Results show that the composites and equally as important the adopted processing are both biocompatible. The quality of filler dispersion in the porous composites was observed by scanning electron (SEM) and atomic force (AFM) microscopies. The biocompatibility of the composites and of the preparation procedure was confirmed by monitoring the cytotoxicity of the composites for different types of cell cultures. Graphical abstract: Image 1